Nafsu dan Id dalam perspektif barat dan Islam - Musyrifah Abdillah (Jurnal Psikologi Terapan, 2019)
In the Islamic view of the passions that encourage us to fulfill all our desires but there is also a good passion and in the western view lust is called id which is innate and the original nature of man, id likened to the ice block at the bottom of the sea which has a very large size it describes human desires are also very expensive. The way we control our lust or id or desire exists by way of Islam and the western way but according to the author the better way of Islam, because Islam that cling to the holy book Al-Quran there are guidelines how humans live. Although each perspective has its own view but now is not the time to stick to what is there but to seek something new.